a, \(2-\dfrac{14}{x}=\dfrac{-22}{3}\)
\(\dfrac{14}{x}=2-\dfrac{-22}{3}=\dfrac{28}{3}\)
\(\dfrac{14}{x}=\dfrac{28}{3}\)
=> \(x.28=14.3\)
\(x.28=42\)
\(x=42:28\)
\(x=\dfrac{3}{2}=1,5\)
b, \(\left(\dfrac{2x}{5}+1\right):\left(-7\right)=\dfrac{1}{35}\)
\(\dfrac{2x}{5}+1=\dfrac{1}{35}.\left(-7\right)=-\dfrac{1}{5}\)
\(\dfrac{2x}{5}=-\dfrac{1}{5}-1=\dfrac{-6}{5}\)
\(\dfrac{2x}{5}=\dfrac{-6}{5}\)
=> \(2x=-6\)
\(x=-6:2=-3\)
a)
\(2-\dfrac{14}{x}=-\dfrac{22}{3}\)
\(\Rightarrow\dfrac{14}{x}=2-\dfrac{-22}{3}=\dfrac{28}{3}\)
\(\Rightarrow x=\dfrac{14.3}{28}=\dfrac{3}{2}=1,5\)
b)
\(\left(\dfrac{2x}{5}+1\right):\left(-7\right)=\dfrac{1}{35}\)
\(\Rightarrow\dfrac{2x}{5}+1=\dfrac{1}{35}.\left(-7\right)\)
\(\Rightarrow\dfrac{2x}{5}+1=-\dfrac{1}{5}\)
\(\Rightarrow\dfrac{2x}{5}=-\dfrac{1}{5}-1=-\dfrac{6}{5}\)
Hay \(\dfrac{2x}{5}=-\dfrac{6}{5}\)
\(\Rightarrow2x=-6\)
\(\Rightarrow x=-\dfrac{6}{2}=-3\)
Chúc bạn học tốt!
a) 2-\(\dfrac{-22}{3}\)=\(\dfrac{14}{x}\)
\(\dfrac{28}{3}\)=\(\dfrac{14}{x}\)
suy ra 28x=14*3
<=> 28x=42
<=>\(\dfrac{3}{2}\)
b) \(\dfrac{2x}{5}\)+1=\(\dfrac{1}{35}\)*-7
\(\dfrac{2x}{5}\)+1=-0,2
\(\dfrac{2x}{5}\)=-1,2
2x=-6
x=-3
mình giúp bạn lần 2 like cái nha